Examining the challenges of people living alone with neurodegenerative conditions: a scoping review protocol - Claire Hulme; Linda Clare; Matthew Prina; Jan R Oyebode; Anthony Martyr; Maria Caulfield; Catherine Charlwood; Laura D Gamble (BMJ Open)
Introduction People living alone with neurodegenerative conditions face unique difficulties in maintaining independence and accessing appropriate health and social care support. Consolidating current understanding regarding these unique difficulties would better inform health and social care services and enable more tailored and appropriate service delivery. The proposed scoping review will summarise evidence from studies that provide evidence about people with dementia, Parkinson’s disease, Huntington’s disease or motor neurone disease who live alone. This protocol sets out the processes that will be followed in the subsequent scoping review to ensure that a transparent, rigorous and reproducible approach is used to identify, select and synthesise relevant evidence.Methods and analysis This scoping review protocol uses well-established methodology outlined by the Preferred Reporting Items for Systematic review and Meta-Analysis and the Joanna Briggs Institute. Relevant publications will be searched using PubMed, Web of Science Core Collection, CINAHL and AgeLine via EBSCOhost and EMBASE, PsycInfo and Social Policy and Practice via Ovid. Grey literature will be searched via Google looking specifically for pdf documents. As there was no previous review on the topic, no date restrictions will be applied to the searches. Piloting of the search strategy provided an estimate of the number of titles likely to require title and abstract screening, which, along with prior experience from a similar review approach, informed the feasibility of the proposed strategy. For research publications, a two-stage screening approach will be undertaken. The first stage will involve screening titles and abstracts for relevant literature on people with neurodegenerative conditions living alone in the community. The second stage will involve full text screening of selected articles. For grey literature, the first 20 PDFs per website identified in Google will be downloaded and screened. Summary data will be extracted from publications selected for inclusion. Data synthesis will involve tabulating study characteristics and findings and preparing narrative summaries to identify commonalities, gaps and areas for future research.Ethics and dissemination Ethical approval is not required for this review, as the information included is in the public domain and people with lived experience are consultees rather than research participants. Consultation with people with lived experience, stakeholders and experts linked with the National Institute for Health and Care Research Policy Research Unit in Dementia and Neurodegeneration University of Exeter will help to ensure the relevance and applicability of findings. Dissemination will include a policy report and peer-reviewed publications aimed at informing policy, practice and improving support services for people living alone with neurodegenerative conditions.